Assessment of environmental degradation of land and its impact on agricultural production in western Iraq - Jassim, Mayada Safaa; Gharbi , Moshtaq Ahmed; Hussein , Adnan Neama; Salh, Abdulqader Mahdi (Journal of Degraded and Mining Lands Management, 2025)
This study aimed to analyze environmental and agricultural changes in Al-Qa'im District (the district center and Al-Ubaidi sub-district) during the period from 2000 to 2023, using spectral indices (NDVI, SAVI, BSI, and LDI) derived from satellite remote sensing data and geographic information systems. The results showed that the region suffers from clear environmental fragility and intense interaction between climatic and human factors, leading to a marked decline in vegetation cover. The area decreased from 953 km² in 2000 to 820 km² in 2023. Barren areas with high BSI values ??expanded from 2,128 to 3,118 km², while severely degraded areas, according to the LDI index, increased from 1,817 to 2,071 km². At the agricultural level, strategic crops have witnessed significant changes. The area under wheat cultivation increased from 36.08 km² to 125 km², with production doubling from 5,551.5 tons to 50,000 tons. While barley remained limited in area, its productivity increased significantly, especially in the Al-Ubaidi sub-district. Maize crops expanded significantly, with the area increasing from 4.2 km² to 45 km², and production increasing from 2,633.5 to 45,000 tons. The study revealed a clear gap between natural potential and human effort, and calls for improved natural resource management efficiency and the adoption of balanced and sustainable development strategies to reduce desertification and improve land productivity.